Rule of Prebiotics Comprising Infant Formula in Treatment of Acute Diarrhea - Ahmed Mohammed Ali Mohsen Al.Husseini; Sabeeha Sahib Hadi Husein Hillawi; Razzaq Abbood Salman Al.Yasari (Genius Journals, 2022)
Acute diarrhoea is a major contributor to infant morbidity and death. Prebiotics are indigestible dietary components that promote the development of beneficial microorganisms like bifidobacteria.
Keywords: acute diarrhea; prebiotic; formula; nondigestible carbohydrates